2007
DOI: 10.1091/mbc.e06-10-0959
|View full text |Cite
|
Sign up to set email alerts
|

Direct Observation of Regulated Ribonucleoprotein Transport Across the Nurse Cell/Oocyte Boundary

Abstract: In Drosophila, the asymmetric localization of specific mRNAs to discrete regions within the developing oocyte determines the embryonic axes. The microtubule motors dynein and kinesin are required for the proper localization of the determinant ribonucleoprotein (RNP) complexes, but the mechanisms that account for RNP transport to and within the oocyte are not well understood. In this work, we focus on the transport of RNA complexes containing bicoid (bcd), an anterior determinant. We show in live egg chambers t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
108
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(122 citation statements)
references
References 60 publications
(55 reference statements)
14
108
0
Order By: Relevance
“…Organelle transport by kinesin-1 along these subcortical microtubule arrays has been proposed to drive ooplasmic streaming, by exerting hydrodynamic forces on the surrounding cytoplasm (8,52). However, surprisingly, the general kinesin-1 cargo adapter KLC and the microtubule minus-end motor dynein are dispensable for fast ooplasmic streaming (7)(8)(9). This independence of KLC and dynein is reminiscent of another function of kinesin-1, microtubule-microtubule sliding, which is also KLC-and dyneinindependent (10).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Organelle transport by kinesin-1 along these subcortical microtubule arrays has been proposed to drive ooplasmic streaming, by exerting hydrodynamic forces on the surrounding cytoplasm (8,52). However, surprisingly, the general kinesin-1 cargo adapter KLC and the microtubule minus-end motor dynein are dispensable for fast ooplasmic streaming (7)(8)(9). This independence of KLC and dynein is reminiscent of another function of kinesin-1, microtubule-microtubule sliding, which is also KLC-and dyneinindependent (10).…”
Section: Discussionmentioning
confidence: 99%
“…Cytoskeletal filaments and molecular motors are major players that generate the forces required for these activities. For instance, kinesin-1 and microtubules have been shown to provide the mechanical forces required in multiple cellular contexts, such as organelle transport (1)(2)(3)(4), ooplasmic streaming (5)(6)(7)(8)(9), and process formation (10)(11)(12)(13)(14)(15).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In Drosophila, DmKHC is required for posterior localization of oskar mRNA [44]. However, in Drosophila oocytes, dynein, but not kinesin, has been reported to actively transport exuperantia, the core component of RNP complex involved in localizing mRNAs [45,46], to ensure proper localization of the RNP complex [45][46][47]. Interestingly, our study showed that exuperantia interacted with BmKinesin-1, a Kinesin-1 member, suggesting that in PSG cells, the exuperantia-associated RNP complex could be transported by KLP BmKinesin-1.…”
Section: Filamentous Tubulin Colocalizationmentioning
confidence: 99%